The Romantic Relationship of Older Women and Younger Men in “I Hear Your Voice,” I Need Romance 3” and “The Woman Who Still Wants to Marry” - Maria Rosalind (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
With the ideology of patriarchy that is still rooted in Korean society, this thesis analyzes the phenomenon of older women and younger men from three different Korean dramas whose characterizations are different from the usual patriarchal system. This thesis aims at revealing how the characteristics that the characters possess are able to make them interested in their relevant partners. The thesis finds out that the younger men do possess different traits from their gender stereotypes but at the same time, they also still maintain the masculinity trait¾they are supportive, obedient and protective. Meanwhile, the older women’s main attraction is that they still act as the nurturers, regardless of their less submissiveness in the relationship. Thus, these characteristics unite and they are still able to make each of them attracted to their partners. Nevertheless, it can be concluded that the differences here are possible because the characters do not particularly believe in and follow the traditional patriarchal system anymore.